New analytical algorithm for calculating the end leakage magnetic field of a 300Mvar synchronous condenser under no‐load condition. Issue 12 (15th August 2021) - Zhu, Erhang; Liang, Yanping; Han, Xiao; Bian, Xu; Wang, Chenguang
Abstract: Aiming at the complexity of end structures in the end region of large synchronous machines, it is difficult to obtain an analytical method for the end leakage magnetic field. In order to solve such a problem, a new analytical algorithm (NAA) considering the influence of the rotor end shaft and air gap is proposed. The mirror image of the rotor end current with the core end plane and the rotor shaft cylinder as mirror surfaces is studied. The air‐gap effect is considered by the equivalent air‐gap current, and the equivalent air‐gap current equation of synchronous machines in the polar coordinate system is derived. Then, a 300Mvar synchronous condenser (SC) is proposed for the first time in China as an example; according to the Biot–Savart law and the superposition principle, the end leakage magnetic field of the SC under no‐load condition is calculated, and the influence of different shaft structures on the end leakage magnetic field is analysed. Finally, the calculation results are compared with the 3‐D finite element method, which verifies the accuracy of the NAA.